Gendering international student migration: an Indian case-study. Issue 8 (11th June 2017) - Sondhi, Gunjan; King, Russell
ABSTRACT: Despite the mainstreaming of gender perspectives into migration research, very few attempts have been made to gender international student migration. This paper poses three questions about Indian students who study abroad. Are there gender differences in their motivations? How do they negotiate their gendered everyday lives when abroad? Is the return to India shaped by gender relations? An online survey of Indian study-abroad students ( n  = 157), and in-depth interviews with Indian students in Toronto ( n  = 22), returned students in New Delhi ( n  = 21), and with parents of students abroad ( n  = 22) help to provide answers. Conceptually, the paper draws on a 'gendered geographies of power' framework and on student migration as an embodied process subject to 'matrices of (un)intelligibility'. We find minimal gender-related differences in motivations to study abroad, except that male students are drawn from a wider social background. However, whilst abroad, both male and female Indian students face challenges in performing their gendered identities. The Indian patrifocal family puts greater pressure on males to return; females face greater challenges upon return.